Low molecular weight blue mussel hydrolysates inhibit adipogenesis in mouse mesenchymal stem cells through upregulating HO-1/Nrf2 pathway. (October 2020) - Oh, Yunok; Ahn, Chang-Bum; Je, Jae-Young
Graphical abstract: Highlights: Blue mussel hydrolysates (BMH) by peptic hydrolysis with anti-adipogenic effect were prepared. BMH with low molecular weight inhibited lipid accumulation. Anti-adipogenic effect is attributed to the activation of HO-1/Nrf2 pathway. Abstract: Blue mussel proteins are a good source of bioactive peptides. In this study, blue mussel hydrolysate (BMH) with anti-adipogenic effect in mouse mesenchymal stem cells (mMSC) was produced by peptic hydrolysis at 1:500 of pepsin/substrate ratio for 120 min. Additionally, BMH with below 1 kDa (BMH < 1 kDa) showed the highest anti-adipogenic effect in mMSC. BMH < 1 kDa increased lipolysis and down-regulated adipogenic transcription factors including peroxisome proliferator-activated receptor gamma (PPARγ), CCAAT/enhancer-binding protein α (C/EBPα), and sterol regulatory element-binding protein 1 (SREBP1). Generation of intracellular reactive oxygen species during adipogenesis was markedly decreased by BMH < 1 kDa treatment, which is attributed to the up-regulation of heme oxygenase-1 (HO-1) through Nrf2 translocation into the nucleus. Moreover, ZnPP, HO-1 inhibitor, treatment abolished BMH < 1 kDa-mediated HO-1 expression and anti-adipogenic effect in mMSCs through down-regulating adipogenic transcription factors. Taken together, BMH < 1 kDa may be a potential ingredient of nutraceuticals and/or functional foods in ameliorating obesity.